2011
DOI: 10.1161/circresaha.111.247635
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-23 Restricts Cardiac Valve Formation by Inhibiting Has2 and Extracellular Hyaluronic Acid Production

Abstract: Objective: To study the role of microRNAs in cardiac valve formation. Methods and Results:We show that zebrafish dicer mutant embryos, lacking mature miRNAs, form excessive endocardial cushions. By screening miRNAs expressed in the heart, we found that miR-23 is both necessary and sufficient for restricting the number of endocardial cells that differentiate into endocardial cushion cells. In addition, in mouse endothelial cells, miR-23 inhibited a transforming growth factor-␤-induced endothelial-to-mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
85
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 30 publications
2
85
1
Order By: Relevance
“…This regulation of Tbx5 is critical to restrict the expression of has2, one of the critical genes for the formation of AVC, in the specific region of the heart tube. The ectopic expression of has2 causes heart malfornations 8,22 , that are very similar to the phenotype of kctd10 mutant. We confirmed that the heart defect in kctd10 mutant is due to the ectopic expression of has2.…”
Section: Kctd10 Directly Binds Tomentioning
confidence: 76%
See 4 more Smart Citations
“…This regulation of Tbx5 is critical to restrict the expression of has2, one of the critical genes for the formation of AVC, in the specific region of the heart tube. The ectopic expression of has2 causes heart malfornations 8,22 , that are very similar to the phenotype of kctd10 mutant. We confirmed that the heart defect in kctd10 mutant is due to the ectopic expression of has2.…”
Section: Kctd10 Directly Binds Tomentioning
confidence: 76%
“…Has2 catalyses the synthesis of hyaluronic acid, the major component of cardiac jelly, thus the cardiac jelly swells at the AVC. Has2 also plays a pivotal role in the epithelium-to-mesenchyme transformation of the endocardium at the AV boundary, which gives rise to the endocardial cushions and valves 22,23,27 . In the forming heart of the kctd10 mutant, Tbx5 is hyperactive due to the absence of functional Kctd10.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations